2018
DOI: 10.1016/j.jaci.2017.12.385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics and prebiotics on immune response to influenza vaccination in adults: A systematic review and meta-analysis of randomized controlled trials

Abstract: Abstract:We conducted a meta-analysis to evaluate the effects of probiotics and prebiotics on the immune response to influenza vaccination in adults. We conducted a literature search of Pubmed, Embase, the Cochrane Library, the Cumulative Index to Nursing and Allied Health (CINAHL), Airiti Library, and PerioPath Index to Taiwan Periodical Literature in Taiwan. Databases were searched from inception to July 2017. We used the Cochrane Review risk of bias assessment tool to assess randomized controlled trial (RCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Studies examining effects of established prebiotics on immune responses to vaccinations against RTI-causing viruses have been collated in two recent meta-analyses. 34 , 35 In the first, prebiotics were found to increase the odds of achieving H1N1 and H3N2, but not B-strain, seroprotection following vaccination, but had no effect on seroconversion rates (Table II ). 34 The second meta-analysis reported that prebiotics increased postvaccination antibody titers for H1N1, but not H3N2 or B strains (Table II ).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Studies examining effects of established prebiotics on immune responses to vaccinations against RTI-causing viruses have been collated in two recent meta-analyses. 34 , 35 In the first, prebiotics were found to increase the odds of achieving H1N1 and H3N2, but not B-strain, seroprotection following vaccination, but had no effect on seroconversion rates (Table II ). 34 The second meta-analysis reported that prebiotics increased postvaccination antibody titers for H1N1, but not H3N2 or B strains (Table II ).…”
Section: Resultsmentioning
confidence: 98%
“… 34 , 35 In the first, prebiotics were found to increase the odds of achieving H1N1 and H3N2, but not B-strain, seroprotection following vaccination, but had no effect on seroconversion rates (Table II ). 34 The second meta-analysis reported that prebiotics increased postvaccination antibody titers for H1N1, but not H3N2 or B strains (Table II ). 35 Only one study included in those meta-analyses was conducted in a healthy non-elderly adult population, and, in that study, no effects of long-chain inulin and oligofructose supplementation on the immune response to vaccination were observed (Table S3).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations